Rare hybrid tumor of odontogenic fibromyxoma and central giant cell granuloma in maxilla: First reported case - Narayan Dutt Pandey; Sushilkumar Balasaheb Bagul; Rajeev Ramesh Talmohite; Amit Kumar Choudhary (Wolters Kluwer Medknow Publications, 2023)
Fibromyxoma is a locally aggressive rare benign tumor of mesenchymal origin with or without odontogenic epithelium. The etiology of this tumor remains unknown and it is responsible for approximately 3-8% of all cysts and tumors. Another locally destructive benign lesion is central giant cell granuloma (CGCG) which contains osteoclast-like multinucleated giant cells. CGCG accounts for about 7% of all benign jaw tumors, which usually affects younger females. A hybrid lesion with histologic features of both central fibromyxoma and CGCG has not been reported in the literature so far. In the present article, we report the first case of a hybrid tumor comprising odontogenic fibromyxoma with CGCG in a female along with a brief review of its clinical presentation, radiographic features, histological features, and management.